2011
DOI: 10.1364/josaa.28.000475
|View full text |Cite
|
Sign up to set email alerts
|

Geometric phase: two triangles on the Poincaré sphere

Abstract: The method of obtaining the dynamic and geometric part of the phase introduced by a birefringent medium in two kinds of interferometric experiments is presented. The mathematical formulas for the phases obtained using Jones formalism are visualized with the specific triangles on the Poincaré sphere. Generally, these triangles are similar to those used in the Pancharatnam's original construction developed by Courtial to calculate the Pancharatnam geometric phase for the light passing through a single birefringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…The theoretical results obtained will help us to interpret the experiments in Sections 3 and 4. First thing to consider is that the phase-difference δ between two beams with a different polarization participating in interference is given by [28]:…”
Section: Theoretical Analysis Of the Interferometric Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theoretical results obtained will help us to interpret the experiments in Sections 3 and 4. First thing to consider is that the phase-difference δ between two beams with a different polarization participating in interference is given by [28]:…”
Section: Theoretical Analysis Of the Interferometric Experimentsmentioning
confidence: 99%
“…In this case, the phase-difference is strictly given by the projection between the two SOPs and thus has a pure geometric origin. This is the so-called geometric phase, which is related to the PancharatnamBerry phase [28], and provides a means to establish when two beams with a different SOP can be considered to be in phase. This distinction between the geometric and non-geometric origin of the phase-difference is of relevance for the purpose of the paper.…”
Section: Theoretical Analysis Of the Interferometric Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…where T and K stand for some constant values (K has a meaning of the contrast for measurements where fringe patterns are applied; see, for example, the setup with the Wollaston compensator described in [11]). Let us note that the argument of the cosine function in Eq.…”
Section: Geometric Phase Calculationmentioning
confidence: 99%
“…Courtial [10] showed that trajectory describing the process of light polarization state transformation can be presented on the Poincaré sphere in a more convenient way using the points representing the birefringent plate's eigenstates. In our previous works, we expanded Courtial's original idea using simultaneously two points representing both, fast and slow, wave plate's eigenwaves [11] and even enhanced this formalism in the case of dichroic media [12]. This allowed us to present the intuitive graphical interpretation of the geometric phase calculation on the Poincaré sphere for some polarization experiments with a wave plate placed inside the Mach-Zehnder interferometer and inside the linear polariscope.…”
Section: Introductionmentioning
confidence: 99%